Strong reduction of colorectal cancer incidence and mortality after screening colonoscopy: prospective cohort study from Germany - Guo, Feng; Chen, Chen; Holleczek, Bernd; Schöttker, Ben; Hoffmeister, Michael; Brenner, Hermann (The American journal of gastroenterology, 2021)
A claimed advantage of colonoscopy over sigmoidoscopy in colorectal cancer (CRC) screening is prevention of CRC not only in the distal colon and rectum but also in the proximal colon. We aimed to assess the association of screening colonoscopy use with overall and site-specific CRC incidence and associated mortality.